Sustainable urban development in a city affected by heavy industry and mining? Case study of brownfields in Karvina, Czech Republic. (1st April 2016) - Martinat, Stanislav; Dvorak, Petr; Frantal, Bohumil; Klusacek, Petr; Kunc, Josef; Navratil, Josef; Osman, Robert; Tureckova, Kamila; Reed, Matthew
Abstract: Due to recent societal changes 'brownfield' sites have gradually become a significant element in planning urban development. Brownfields can occur as a barrier and obstacle to the development of the urban organism but simultaneously they also represent unrealised potential. Brownfields, ex-industrial sites, are greater in those cities whose development was based on heavy industry or mining. In the first part of this paper theoretical concepts linked to the regeneration of brownfields are discussed, the second part is devoted to a case study of Karvina, in the Czech Republic, where the driving forces behind the occurrence of brownfields, their spatial distribution, and their prospects for regeneration are analysed. It was found that 28 brownfield sites on 121 ha are located in surveyed city with the majority having industrial and mining origins. Majority of local brownfields are owned by a local mining company. The perception of individual sites by the local population was ascertained via a questionnaire survey (n = 150). This found that awareness about problems connected to brownfields is quite limited and that local population perceive post-mining brownfields, located in more distant locations, as an opportunity for new industries to create job opportunities in city with significant unemployment problems. Highlights: Brownfield sites and associated impacts on the urban development of post-industrial cities. The popularity of industrial usage for post-mining brownfields. That post-mining landscapes are frequently not perceived as brownfield. Brownfields located in the peripheral locations are usually disregarded. The central role of public administration in brownfields regeneration projects.